An Instrument to Assess the Organizational Climate of Agile Teams - A Preliminary Study - Dutra, Eliezer; Lima, Patricia; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
Background: Organizational climate surveys allow the access to the opinions, preferences, or dissatisfactions of the team members of their working conditions. Understanding how different factors influence the organizational climate of agile software development teams can be challenging for organizations. TACT is an instrument to assess the organization climate of agile teams. Its initial version comprises the Communication, Collaboration, and Leadership dimensions. Objective: We present the preliminary evaluation of TACT. Method: We planned and executed a case study considering two development teams. We evaluated TACT using open-ended questions, quantitative methods, and TAM dimensions of Intention to Use, Perceived Usefulness, and Output Quality. Results: TACT allowed to classify the organizational climate of both teams as positive for the Collaboration, Communication, and Leadership dimensions. However, some items were assessed negatively or neutrally which represent attention points. TACT captured the lack of agile ceremonies, the difficulty of the product owner in planning iterations, and the distance in leadership. In addition, TACT presented high levels of reliability. Conclusions: TACT captured the organizational climate of the teams correctly. The team leaders reported intention of future use. The items that compose TACT can be used by researchers investigating the influence of human factors in agile teams, and practitioners that need to design organizational climate assessments of agile teams.